THE STRATEGIES OF TIANGGE SELLERS TO THE PURCHASING INTEREST OF THE MARKET - Blas, Fe Atanacio; Erestain, Charelome (PEOPLE: International Journal of Social Sciences, 2018)
This study was conducted in order to highlight the growing ‘tiangge’ industry in the municipality of Taytay, Rizal Philippines where certain dynamics were observed in and between the seller and its clients in the areas of selling and its strategies. Drawn basically from the perspective of the sellers, this research evaluated the kind, style, selling scheme, price and frequently asked questions (FAQ’s) about ready-to-wear (RTW) products and other related commodities sold in Taytay tiangge. The researchers used the Bottom of the pyramid theory, Defensive marketing theory and Consumer Theory which are common and most effective theories when it comes to strategies implementation for Flea Markets, Bazaars and Tiangge in the modern day. Through descriptive statistics, it was underscored that the top-selling kind of RTW was blouses for women in the price range of 100-150 Php. (Philippine Peso) by wholesale and retail quantities. Other kinds of RTW/commodities include undergarments, curtains, bed sheets, shoes and bags in which the sellers variably offer together with the RTW products. Through a Chi-Square test, the variables drawn from the sellers’ perspective (kinds of RTW products sold, styles of RTW products sold, the selling scheme, and the price range of the RTW products) were correlated to the variables drawn from the purchasing interest of the market (bestseller RTW products sold according to kind, bestseller RTW products sold according to styles, the customers’ scheme of purchasing, price reference of the customers and their frequently asked questions); showing thus the positive significant effects on all variables except on style. Thus, in this study the researchers concluded that the strategies of the sellers are relative to the purchasing interest of the market. However, due to limitations stipulated within the duration of the study, it is further interesting to revisit the other aspect/dynamism of differences between females and males in terms of preferred kinds, styles, quantity and price. Furthermore, a comprehensive study should follow through in the interest of the municipality in the advent of ‘tiangge’ as a thriving industry that could potentially help sustain the local economy.